Analysis of the Beginning of Political Dynamics in the Era After the Death of the Prophet Muhammad - Basri, Muhammad; Manullang, Annisa Zakhra; Siregar, Riska Anita; Suseno, Raihan Nazrey (Lembaga Riset Mutiara Akbar, 2024)
This study delves into the life history of Prophet Muhammad through a qualitative literature review approach. The research focuses on his childhood, youth, revelation, significant historical events, social and moral contributions, as well as his legacy and influence. The theoretical review encompasses key aspects such as Islamic theology, moral teachings, social concepts, and the role of women in Islam. Through the collection and analysis of data from various literary sources, this research aims to provide a profound understanding of the values of Islamic teachings inherited from Prophet Muhammad, his contributions to shaping society, and the impact on Islamic civilization.